2021
DOI: 10.21273/hortsci15551-20
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Phytochemical Content of 22 Pomegranate (Punica granatum) Varieties

Abstract: Pomegranate is a drought-tolerant and salt-tolerant crop. Its fruits contain high levels of phytochemicals that have many health benefits. Pomegranate has the potential to be an alternative crop in areas where water availability is limited, such as west Texas. However, more than 500 pomegranate varieties are estimated to exist worldwide, and little is known about which varieties are suitable for growing in the west Texas region. Therefore, the objective of this study was to evaluate the field performance of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Regarding the juices, our results on total soluble phenolic compounds are generally higher than those reported in the literature, but very close to the contents found for wild Montenegro genotypes (4.4-8.5 mg•g −1 fw) [27,39,42,43]. Lower levels of total soluble phenolic compounds were also reported by Ferrara et al [22] for juices extracted from Ako (1.77 mg•g −1 fw), Emek (1.50 mg•g −1 fw), and Wonderful One (2.34 mg•g −1 fw) cultivars grown in the same orchard as this study, but in previous years.…”
Section: Functional Quality Attributessupporting
confidence: 82%
“…Regarding the juices, our results on total soluble phenolic compounds are generally higher than those reported in the literature, but very close to the contents found for wild Montenegro genotypes (4.4-8.5 mg•g −1 fw) [27,39,42,43]. Lower levels of total soluble phenolic compounds were also reported by Ferrara et al [22] for juices extracted from Ako (1.77 mg•g −1 fw), Emek (1.50 mg•g −1 fw), and Wonderful One (2.34 mg•g −1 fw) cultivars grown in the same orchard as this study, but in previous years.…”
Section: Functional Quality Attributessupporting
confidence: 82%
“…However, analysis of seasonal and yearly variations might be useful for gathering information for stable production. The wide variability in both qualitative and quantitative traits found in this study might be useful for identifying genotypes and might be required for the genetic improvement of crops [23,42]. The genetic analyses showed that the differential expression of a number of genes located in chromosomes 1, 2, and 7 are responsible for the differences in root characteristics of carrots [43,44].…”
Section: Variation In Qualitative and Quantitative Morphological Traitsmentioning
confidence: 69%
“…The genotypes whose fruit juices contain more phenolic compounds, lower total soluble solids, and more acidic pH have higher antioxidant activity. A positive correlation between antioxidant activity and phenolic compounds content was reported in previous studies [54,89,90]. Reduction in the phenol content in some pomegranate genotypes might coincide with the increase in anthocyanin pigment content due to the contribution in the biosynthesis of the flavylium ring during the formation of anthocyanin [91,92].…”
Section: Correlation Between Targeted Metabolites and Morphological T...mentioning
confidence: 56%